Is public bike-sharing feasible in Ghana? Road users' perceptions and policy interventions. (January 2023) - Alimo, Philip Kofi; Agyeman, Stephen; Danesh, Ali; Yu, Chunhui; Ma, Wanjing
Abstract: Public bike-sharing is common in many regions, but rare in sub-Saharan Africa. Despite the myriad of advantages, only five African countries have implemented it. Besides, road user perceptions of novel bike-sharing implementation remain underrepresented in the extant literature. The lack of data in sub-Saharan Africa makes planning and implementation difficult. To fill this gap, this study investigates 600 road users' perceptions of a proposed novel bike-sharing scheme in Ghana's two largest cities. The study employed the Theory of Planned Behavior to formulate a structural equation model. Overall, road users showed interest in adopting future bike-sharing schemes. However, this is dependent on cycling infrastructure and policies. Consequently, policies must address social norms, cycling interests, cycling training, pricing, station locations, and safety. Age, education, and bike ownership significantly affect intentions to adopt. These findings reinforce the need for a national cycling policy framework and enhanced transport infrastructure to support active mobility in Ghana. Highlights: Bike-sharing feasibility was studied in Ghana using 600 road users' perspectives. The Theory of Planned Behavior was employed to formulate structural equation model. Road users in Kumasi and Accra showed interest in adopting bike-sharing schemes. Age, education, and bike ownership significantly influence ridership intention. Bike-sharing would require enhanced cycling infrastructure and policies.